2009
DOI: 10.1002/jcla.20289
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a cut‐point value of serum TNF‐α levels in the metabolic syndrome

Abstract: Cardiovascular diseases and type 2 diabetes are the major causes of mortality in Mexico. Metabolic syndrome (MS) is a cluster of factors that increase the risk to develop such diseases. Previous studies have shown that MS is associated with high tumor necrosis factor (TNF-a) levels. In fact, TNF-a has been proposed to be a useful marker for clinical diagnosis of inflammation at an early stage. Therefore, we analyzed TNF-a concentrations in Mexican individuals with or without MS and related these levels to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
3
7
0
1
Order By: Relevance
“…These mechanisms may partly explain the reduced plasma CRP concentrations with MedDiet in the absence of weight loss even when other proinflammatory cytokines are not significantly altered. Although in our study plasma IL-18 concentrations on the control diet were comparable to those obtained in other populations with MetS, plasma IL-6 and TNF-a concentrations were much lower (about 40-50%) and this may also account for the lack of effect of the MedDiet without weight loss on these proinflammatory markers (11,29,30). Finally, we cannot exclude the possibility that the small reduction observed in plasma IL-6, IL-18, and TNF-a would have been significant with a greater number of subjects.…”
Section: Discussionsupporting
confidence: 70%
“…These mechanisms may partly explain the reduced plasma CRP concentrations with MedDiet in the absence of weight loss even when other proinflammatory cytokines are not significantly altered. Although in our study plasma IL-18 concentrations on the control diet were comparable to those obtained in other populations with MetS, plasma IL-6 and TNF-a concentrations were much lower (about 40-50%) and this may also account for the lack of effect of the MedDiet without weight loss on these proinflammatory markers (11,29,30). Finally, we cannot exclude the possibility that the small reduction observed in plasma IL-6, IL-18, and TNF-a would have been significant with a greater number of subjects.…”
Section: Discussionsupporting
confidence: 70%
“…MS is considered to be a chronic inflammatory status. Previous studies reported that the subjects with MS have a higher inflammation status and that a higher level of CRP (≥1.0 mg L −1 ), IL‐6 (≥1.5 pg L −1 ), or TNF‐α (≥1.36 pg mL −1 ) may increase the risk of MS . In the present study, in either the placebo or WGP group, subjects with MS had higher levels of inflammatory markers at baseline (Table ).…”
Section: Resultssupporting
confidence: 44%
“…7 MS is considered to be a chronic inflammatory status. Previous studies reported that the subjects with MS have a higher inflammation status and that a higher level of CRP (≥1.0 mg L −1 ), IL-6 (≥1.5 pg L −1 ), or TNF-(≥1.36 pg mL −1 ) may increase the risk of MS. 5,23 In the present study, in either the placebo or WGP group, subjects with MS had higher levels of inflammatory markers at baseline ( Table 2). Inhibition of inflammation by antioxidants thus constitutes an important mechanism in MS. Nuclear factor-B (NF-B) is generally considered to be a pro-inflammatory transcription factor and plays a critical role in the development of inflammation.…”
Section: Correlations Between Inflammatory Markers and Antioxidant Enmentioning
confidence: 53%
“…The findings of the study allow us to believe that it is justifiable to monitor serum TNFa concentrations in children and adolescents with T1DM during the course of the disease to predict the occurrence of diabetic microangiopathy. A similar threshold serum value for TNFa in patients with the metabolic syndrome was determined by Gurrola-Diaz et al [50]. The threshold value for serum TNFa was set at the level of 1.36 pg/ml.…”
Section: Discussionmentioning
confidence: 97%
“…The sensitivity and specificity were 78.1% and 61.5%, respectively. The authors suggest that the measurement of TNFa serum levels may be clinically useful as a prognostic marker while diagnosing the metabolic syndrome [50].…”
Section: Discussionmentioning
confidence: 99%